I love my tutu! - Gilbert, Frances 1969-; Unten, Eren Blanquet (New York Random House, 2019)
A young girl learns that there is a time and a place for everything, including wearing her beloved tutu
English Stories
Keywords: Clothing and dress -- Fiction; Tutus (Ballet skirts) -- Fiction